Shadow Education in the Era of Industrial Revolution 4.0 It’s Disruptive Impact on Islamic Religious Education Institutions in Indonesia - Rahmat Hariadi; Ratih Kusuma Ningtias; Sifwatir Rif’ah; Anjani Rohmatul Maula (MADINAH, 2026)
The Fourth Industrial Revolution has driven significant transformations in the world of education, including the emergence of the phenomenon of digital technology-based shadow education. Platforms such as Ruangguru, Zenius, and Quipper offer flexible, personalized, and technology-based non-formal learning models, thereby changing students’ learning patterns in the digital age. This study employs a conceptual library research approach by analyzing various academic literature, scientific journals, and documents related to digital education transformation and Islamic Religious Education (IRE). The findings indicate that shadow education has implications for changes in the role of IRE teachers, the transformation of digital pedagogy, the development of adaptive curricula, and the digitization of institutional management in Islamic education. The literature analysis also indicates that the main challenges faced by PAI institutions include limited technological infrastructure, low digital literacy among educators, and the potential for religious misinformation in digital spaces. On the other hand, digital transformation opens opportunities for the development of PAI learning that is more interactive, flexible, and contextual, in line with the needs of the digital generation. The novelty of this research lies in an integrative analysis of the relationship between shadow education, digital transformation, and PAI institutional adaptation within the framework of the Fourth Industrial Revolution and Society 5.0. This research contributes by developing a conceptual framework for PAI transformation that emphasizes integration This study contributes by developing a conceptual framework for the transformation of Islamic Education that emphasizes the integration of digital technology, pedagogical innovation, and the reinforcement of Islamic values within the Islamic education system in the digital age